Relevansi Informasi Akuntansi terhadap Harga Saham pada Sektor Pertambangan: RELEVANSI INFORMASI AKUNTANSI TERHADAP HARGA SAHAM PADA SEKTOR PERTAMBANGAN - Febriyanti, Fanny (LPPM Universitas Negeri Jakarta, 2023)
Abstract The purpose of this study is to determine the relevance of the values of accounting information to the company's stock price. Each company does not provide direct authority in providing company financial information to external groups, namely investors and creditors. Therefore, they rely on information in the form of financial reports provided by management. The theory used in this research uses clean surplus theory, market efficiency theory, signal theory, and value relevance theory. Clean surplus theory provides assumptions about how to show the market value of a company based on the values contained in the balance sheet and income statement. The theory of market efficiency explains the security prices with published accounting information have value relevance. Signal theory explains the signal from the sender (the owner of the information) which provides relevant information to the receiver that is useful for increasing decision-making power. Value relevance theory explains about an information that is used to explain or describe the values of the company. This study uses secondary data observation techniques obtained from the annual financial statements of mining companies listed on the Indonesia Stock Exchange for the period 2012-2021. This research using a non-probabilistic sampling technique, using a purposive sampling method where in this method the sampling uses certain criteria. The total sample obtained reached 120 research samples. The data analysis techniques used include descriptive statistical analysis, coefficient similarity test, classical assumption test, multiple linear regression analysis, F statistic test, t statistic test, and coefficient of determination test. The results showed that the F test (α = 0.05) obtained a significance value of 0.000 so it can be said that the test is acceptable. Based on the t test, the value of significance Book Value Per Share (BVPS), Investing Cash Flow (CFINV), and Financial Cash Flow (CFFIN) each of 0.000, 0.000 and 0.010 so that H2, H4, and H5 are accepted. However, the value of significance for the Earning Per Share (EPS) and Operating Cash Flow (CFOPS) variables each of 0.144 and 0.304 so that H1 and H3 are rejected.